Fast and comprehensive characterization of chemical ingredients in traditional Chinese herbal medicines by extractive atmospheric pressure photoionization (EAPPI) mass spectrometry. (9th August 2017) - Liu, Chengyuan; Wen, Wu; Shao, Jun; Zhao, Wan; Qi, Keke; Yang, Jiuzhong; Pan, Yang
Abstract : Rationale: The goal of this work is to employ extractive atmospheric pressure photoionization mass spectrometry (EAPPI‐MS) to characterize the constituents in traditional Chinese herbal medicine (TCHM) directly without chromatographic separation. Methods: Sample was placed in 4 mL of methanol/water (v/v, 3:1) in the nebulization cell, and then the ultrasonic nebulizer was switched on. The ultrasonic nebulization system allows the simultaneous sample extraction and introduction of extract aerosols. The extract aerosols were vaporized in a transfer tube. Mixed with a gaseous dopant, vaporized analytes were ionized through ambient photon‐induced ion–molecule reactions, and were mass‐analyzed by high‐resolution time‐of‐flight mass spectrometry (TOF‐MS). Results: The major ingredients including alkaloids, flavonoids, amino acids, saccarides, ginsenosides, lignans and terpenoids were readily detected. Compared with electrospray ionization (ESI), EAPPI allowed the ionization of a wider range of compounds, which is desirable for the integral characterization of TCHMs containing numerous constituents. The significant discrepancies for both alkaloids and terpenoids in tripterygium glycoside tablets from two different manufacturers could be simultaneously reflected from EAPPI mass spectra. Conclusions: Our results demonstrate that EAPPI‐MS can be regarded as a supplementary ambient method for the fast and comprehensive analysis of TCHMs, which is important for the quality control and safety assurance of these products.